The Impact of Multinational Enterprises on Global Governance: The Protests Movement View - Achaku, Mark; M.C., Ihionu q; Igwe, Anthony Aniagbaoso (International Journal Of Management And Economics Invention, 2021)
This study which is based on secondary data and looks at the activities of Multinational Corporation and its impacts, global governance, protests movement and the future of global governance. Available data show that multinational corporation derives at least a quarter of its revenue outside its home country. However, the debate is how significant do they contribute to development or involve in activities that lead to human and economic deprivation of host communities. The study reveals that the benefits are not enough compared to the damages. The multinational corporation uses global governance institutions to back up their interests and always get preferred treatment. The host communities who feel exploited are not happy but the multinational corporations are always innovative so, there is hope towards finding solutions. In this regard therefore, the relevant stakeholders should be engaged towards collective decision making and problem-solving in a participatory manner for effective global governance.